SPREADING AND DEVELOPMENT OF FIG LEAF ROLLER (CHOREUTIS NEMORANA HB.) IN FERGHANA VALLEY (Scientific journal of the Fergana State University, 2023)
This article discusses the detailed description, development and dissemination of fig molellister in Fergana Valley. Moreover, based on the analysis, the time period for the conversion of fig leaf roller from larvae to moth and the degree of damage to various varieties of figs is shown.